Neural mechanisms of attention involved in perception and action: From neuronal activity to network - Tetsuo Kida; Ryusuke Kakigi (Journal of Physical Fitness and Sports Medicine, 2015)
In everyday life, attention is adaptively directed to a stimulus and action in multisensory environments. Recent studies have demonstrated that the functionality of attention and related brain activities are improved by exercise and sports activities. We herein reviewed our previous studies on the neural mechanisms of attention using magnetoencephalography (MEG) and electroencephalography (EEG) (MEEG). MEEG non-invasively records the synchronous activation of neuronal populations from the whole brain of a human as a magnetic field or electric potential with high temporal resolution to the order of milliseconds; and, thus, is a powerful tool for investigating the spatio-temporal dynamics underlying the modulation of real neuronal activities. We presented MEEG data on the neural representations of within-modal, intermodal, cross-modal spatial attention as well as somatic-motor interactions; these were discussed in terms of the effects of attention directed to a stimulus and action on early sensory processing. We also discussed a recent study on attention using a relatively new analysis technique (graph-theoretical or complex network analysis) in human neuroimaging to demonstrate the spatio-temporal dynamics of the functional properties of the human brain network underlying attentional control. These findings support the hypothesis that early sensory processing in modality-specific cortices is regulated, irrespective of the sensory modality, by attentional control signals from the lateral prefrontal cortex, which operates as an important center controlling the flow of information in the human brain.